PENGARUH PENERAPAN MODEL PEMBELAJARAN AKTIF TIPE LEARNING START A QUESTION (LSQ) TERHADAP HASIL BELAJAR SENI TARI DI SMA NEGERI 14 PADANG - Vebbi Vebiola; Yuliasma Yuliasma; Zora Iriani (SENDRATASIK UNP, 2017)
AbstractThis article the aim to investigate the effect of implementing Learning Start with Question (LSQ) type of Active Learning model toward students’ learning outcome in learning Dance at SMA Negeri 14 Padang in academic year 2016-2017. This study was experimental research with the static group comparison design. The population of this study was 255 XI grade students of SMA Negeri 14 Padang registered in academic year 2016-2017. The sample was determined by using purposive sampling technique in which XI IPS3 was chosen as experimental class and XI IPS 1 was as control class. There were 32 students of each class. The instrument used was cognitive test. The result showed that there was significant difference between the implementation of Learning Start with Question and that of conventional method. The average score of experimental class (83.03) was higher than that of control class (76.78). It can be seen that tcount was 4.31 and ttable was 1.67. This result meant the hypothesis was accepted. Therefore, there was better effect of implementing Learning Start with Question than that of conventional method.Keywords: Influence, Learning Model, Learning outcomes.